2016
DOI: 10.1159/000446004
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Thrombolysis in Cervical Artery Dissection-Related Ischemic Stroke: A Meta-Analysis of Observational Studies

Abstract: Background: Although thrombolysis is considered to be the first-line treatment for ischemic stroke, there remains an ongoing controversy on the safety and efficacy of thrombolysis in cervical artery dissection (CAD). The aim of this meta-analysis was to assess observational data related to the safety and efficacy of thrombolysis in CAD-related ischemic stroke. Methods: We performed a systematic search of the efficacy of thrombolysis treatment in CAD-related ischemic stroke with appropriate observational studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…The use of thrombolytics is controversial, but may also be considered for patients presenting with stroke resulting from vertebral artery dissections. While not directly studied in VAD, a recent metanalysis of thrombolysis in ischemic stroke caused by cervical artery dissection (which includes both carotid and vertebral dissection-related stroke) found that thrombolysis in patients has comparable safety and functional outcomes to thrombolysis in patients with non-dissection-related strokes [ 2 ]. However, further randomized controlled trials (RCT) need to be performed to assess the safety and efficacy of thrombolytics in strokes caused solely by VAD, prior to routine use of thrombolysis in these patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of thrombolytics is controversial, but may also be considered for patients presenting with stroke resulting from vertebral artery dissections. While not directly studied in VAD, a recent metanalysis of thrombolysis in ischemic stroke caused by cervical artery dissection (which includes both carotid and vertebral dissection-related stroke) found that thrombolysis in patients has comparable safety and functional outcomes to thrombolysis in patients with non-dissection-related strokes [ 2 ]. However, further randomized controlled trials (RCT) need to be performed to assess the safety and efficacy of thrombolytics in strokes caused solely by VAD, prior to routine use of thrombolysis in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment options include anticoagulation or antiplatelet therapy. In patients with signs of acute ischemia, intravenous thrombolysis or endovascular intervention may also be indicated [ 2 - 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…We applied the combination of Begg’s and Egger’s tests to assess the presence of publication bias. The P ‐value of Begg’s test and/or Egger’s test <.05 indicated the presence of publication bias 23 . The pooled risk ratio (RR) and 95% CI for categorical data were calculated using the Mantel–Haenszel statistical method.…”
Section: Methodsmentioning
confidence: 99%
“…In 2016, a systematic literature review across 10 observational studies reporting on 174 IVT-treated CeAD patients and 672 CeAD patients treated without IVT (control group) 21 showed that the likelihood of favorable outcome (i.e. mRS 0, 1, 2) and the odds for an excellent functional outcome (i.e.…”
Section: Acute Recanalization Therapies: More Work To Be Donementioning
confidence: 99%